Modification and performance evaluation of KAU pepper thresher - AMBUJAN C. V RAVIKUMAR C; Er. George Mathew (Guide) (Tavanur 1993 Department of Post-Harvest Technology and Agricultural Processing)
Modification and performance evaluation of KAU pepper thresher
Modification and performance evaluation of KAU pepper thresher